Improving opportunities and equity in home ownership through the tax system - Pope, Jeffrey; Rowland, Patrick (Taxation Institute of Australia, 2008)
Housing affordability and equity within the housing sector is currently subject to a high level of media coverage and political debate. The controversy centres on difficulties for young households trying to purchase their first house at a time when the wealth of many home owners has grown dramatically with rising house prices. Despite the media attention, there is relatively little recent research into addressing the growing inequity in housing wealth. This paper seeks to redress this imbalance. Current taxation and tax expenditures on housing in Australia are succinctly reviewed, followed by discussion of the so-called ?crisis? in housing affordability and the various measures that have been proposed and/or implemented to date. The main parts of the paper present proposals for a taxation offset for first time home buyers and the application of capital gains tax to higher valued owner-occupied housing. Initial estimates of the overall net tax revenue implications of the combined proposals are presented, and show that after five years the overall package is about revenue neutral. This compares well with the current high transparent and hidden subsidies to all sectors of the Australian housing market. The main challenges in implementation are considered, followed by some concluding comments and suggestions for further analysis.